The Biomechanical Comparison between Two Methods of K-wire Fixation in Extra-articular Distal End Radius Fracture - Parithooran Sembagoundanvalasu Karmegan; Kesavram Alagirisamy; Amudha Ganesh Selvaraj; Muthukumaran Vaiyapuri; Rex Chandrabose (Journal of Orthopedics and Joint Surgery)
Aim: The aim of our study is to compare the biomechanical strength of two different K-wire fixation methods for extra-articular fractures of the distal end of the radius. Materials and methods: This study was performed on 20 artificial distal radius fracture bone models (Synbone®, Switzerland), which were randomly divided into two groups and fixed with three K-wire fixation concepts. Group I underwent the “single styloid double dorsal (SSDD), Manchester technique” of K-wire fixation, and group II underwent the “cross K-wire, AO technique” of fixation. Each configuration underwent testing by three-point bending in different planes and axial compression. Result: In our study results, we determined that the “SSDD” K-wire fixation technique provided the stiffest construct in bending force compared to the AO technique. No difference was noted in the load to failure during axial compression. Conclusion: This study confirms the biomechanical superiority of the SSDD (Manchester) technique of K-wire fixation compared to the cross K-wire (AO) technique for extra-articular distal end radius fractures and justifies the clinical use of this method to prevent loss of reduction or early implant failure.